2019
DOI: 10.3389/fimmu.2019.02626
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Secretory RNases: Focus on Their Oligomerization to Design Antitumor Drugs

Abstract: Ribonucleases (RNases) are a large number of enzymes gathered into different bacterial or eukaryotic superfamilies. Bovine pancreatic RNase A, bovine seminal BS-RNase, human pancreatic RNase 1, angiogenin (RNase 5), and amphibian onconase belong to the pancreatic type superfamily, while binase and barnase are in the bacterial RNase N1/T1 family. In physiological conditions, most RNases secreted in the extracellular space counteract the undesired effects of extracellular RNAs and become protective against infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 325 publications
0
26
0
Order By: Relevance
“…In any case, the significant anti-tumor activity exerted by the N-dimers in both human MeWo and A375 melanoma cell lines, as well as the activity of C-dimers vs. A375 cells, can represent a seed to develop new non mutagenic therapies to counteract with pt-RNases tumors that are presently still incurable [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In any case, the significant anti-tumor activity exerted by the N-dimers in both human MeWo and A375 melanoma cell lines, as well as the activity of C-dimers vs. A375 cells, can represent a seed to develop new non mutagenic therapies to counteract with pt-RNases tumors that are presently still incurable [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…ANG is a small ribonuclease. The cellular function of ANG is intriguing and largely attributes to its ability to transactivate ribosomal RNA in the nucleoli and tRNA cleavage activity [41]. Notably, it was recently demonstrated that ANG binds to its receptor Plexin-B2 and exerts mitogenic activity through multiple kinase pathways that include ERK, AKT, and RAC [42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ANG could function in cell membrane, cytosol, and nucleoli. Moreover, modification of ANG affects its cellular activity [41]. These properties may partly explain why ANG has cytotoxic or proliferative activities, depending on the contexts and cell types [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Secretory RNases are a vast group of enzymes that were initially considered as mere non-specific degradative proteins and that today are known to participate in a wide spectrum of biological activities (a very well-described review of these activities has been recently provided by Gotte and Menegazzi [ 5 ]). These RNases, found in eukaryotic and prokaryotic organisms, are secreted or accumulate inside cellular structures associated with secretory pathways, and therefore they can be found in spaces that are not normally associated with the presence of RNA.…”
Section: Secretory Ribonucleases Display a Vast Array Of Functionsmentioning
confidence: 99%